The Interpretability of Contextual Classifier Ensemble - Jakubczyc, Janina A. (Możliwości interpretacyjne kontekstowego klasyfikatora złożonego, 2010)
While decision trees are usually claimed to be easily interpretable, one cannot say this about decision tree ensembles. Dominant feature of decision tree ensembles is the loss of an interpretability. The aim of this paper is to overcome this issue of comprehensibility by using contextual classifier ensemble.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 104, s. 89-98
Keywords: decision tree; tree ensembles; contextual classifier ensembles; interpretability of classifier ensembles